Middle-Aged Gay Men, Ageing and Ageism - Simpson, Paul. author. aut Link
X, 264 p.
Keywords: Is midlife for gay men the start of a slide towards the rejection, exclusion and misery associated with the spectre of the lonely old queen? Whilst exclusion is possible as gay men age, Middle Aged Gay Men, Ageing and Ageism offers a more nuanced view of gay ageing, using sociological tools to advance understanding beyond stereotypes.